Pengembangan Multimedia Pembelajaran Larutan Elektrolit Dan Non Elektrolit Berbasis Multipel Representasi Menggunakan Lectora Inspire - Muhammad Iqbal; Abdul Hadjranul Fatah; Syarpin Syarpin (Jurnal Ilmiah Kanderang Tingang, 2020)
This study aims to determine the content and feasibility of Lectora Inspire learning multimedia based on multiple representations of electrolyte and non-electrolyte solutions. This multimedia learning is a combination of text, images, animation, and video. This multimedia development learning based on multiple representations uses the Four-D (4D) model adapted from Thiagarajan. This development research only reaches three stages, namely define, design and develop. The data needed in this study is the suitability of concept label data with the 2013 curriculum syllabus, the suitability of learning multimedia content using the concept label checklist, narrative and typology as well as product test result data using student response questionnaires. The instruments used to obtain the data are the concept label identification table with the 2013 curriculum syllabus, the concept label identification table, narration and typology, the concept label conformity checklist, narrative and typology, and the response questionnaire. Product trials were conducted on the 2018 chemistry students to determine the feasibility of students for multimedia that had been developed. Multimedia learning based on multiple representations using lectora inspire consists of home pages, instructions for using multimedia, how to read navigation content and materials for electrolyte and non-electrolyte solutions. The contents of multimedia content on electrolyte and non-electrolyte solution material consist of seven concept labels. The average individual product trial results are 93.2%. While the average product trial results in groups of 93.6%.